EDUCATIONAL INTERACTION OF THE STUDENTS WITH BEHAVIORAL DISORDERS IN THE CONTEXT OF TRANSFORMATION OF EDUCATIONAL PARADIGMS: THE CASE OF AN EDUCATIONAL CENTRE - Galkiene, Alvyra; Kulakauskienė, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article analyses the manifestation of educational interaction among fourteen – eighteen – year – old students with behavioral disorders that are being educated in the socialization centre. The method of a structured interview has been applied in order to determine the peculiarities of such interaction in the contexts of the traditional and the progressive education, prioritizing the culture of cooperative learning culture as a prerequisite for fostering social relations and learning a proper social behaviour. The discourse of the students, teachers and providers of special educational assistance has been analyzed in the context of the lesson organization, cooperation activities and surmounting impediments. The study results revealed that feelings of dignity and belonging to the community are of particular importance for the students of the social centre. However, the education here is based more on the teaching than on the learning strategy, as well as on a vertical interaction between teachers and students. Progressive education episodes, flexible organization of education and joyous atmosphere during the lessons establish a horizontal relationship and reduce tension in the educational environment.